Legalitas Putusan Mahkamah Konstitusi Nomor 90/PUU-XXI/2023 Tentang Pengujian Undang-Undang Nomor 7 Tahun 2017 Tentang Pemilihan Umum - Farizaldi, Muhammad; Indra, Mexsasai; Junaidi, Junaidi (Jurnal Ilmiah Wahana Pendidikan, 2026)
Nowadays, developments in the legal aspect have created many changes to the conditions of government in a country. One of the major changes currently being highlighted by the public in Indonesia is the role of the judiciary, namely the Constitutional Court (MK). The public's great attention to the Constitutional Court cannot be separated from several incidents that occurred, one of which was regarding the Constitutional Court's decision regarding the age limit requirements for vice presidential candidacy which became big news recently. The spotlight on the Constitutional Court and criticism was leveled as a result of the Constitutional Court's decision regarding the legal material being reviewed (judicial review) which was deemed political and full of interests. A code of ethics is a compass that points the moral direction for legal professionals and at the same time also guarantees the moral quality of the legal profession in the eyes of society. It contains a list of special obligations for each member of the legal profession to regulate their behavior in society and is expected to be adhered to firmly by all members of the legal profession. This research wants to look at the legality aspect of Constitutional Court Decision Number 90/PUU-XXI/2023 concerning Review of Law Number 7 of 2017 concerning General Elections regarding the age limit for nominations for Presidential and Vice Presidential candidates in Indonesia. This research is normative legal research. This is based on library research which takes quotations from reading books, or supporting books that are related to the problem to be researched. Add data sources. Primary, secondary and tertiary data sources are characteristic of this research. This research also uses qualitative data analysis and produces descriptive data From the results of the research and discussions carried out, several conclusions were obtained, namely: First, the decision regarding the age limit for candidacy for presidential and vice presidential candidates is different from previous decisions that examined the same subject matter. This shows the Constitutional Court's inconsistency in decision making. In the author's opinion, there is an alleged conflict of interest behind the Constitutional Court Decision No. 90/PUU-XXI/2023. However, on the other hand, the Constitutional Court's decision must be interpreted as a legal norm that applies and has legality that has permanent legal force. Second, the Constitutional Court's final decision is attached to the essence of the Constitution's position as the highest law so that no other law has a higher position than it.